PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SDN 2 ULIM PIDIE JAYA - Hafni Zahara; Aulia Rahmadani; Marlinda Marlinda; Nurhadia Nurhadia (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
Clean and healthy living behavior (PHBS) is a series of actions implemented based on awareness, which is the result of the learning process. This behavior is key to shaping individuals, families, groups, or communities capable of maintaining their own health and actively contributing to creating optimal health conditions in their surroundings. For example, PHBS activities are carried out at SDN 2 ULIM involving 29 students from the 6th grade. The students' participation in these activities proves that health education significantly contributes to improving their understanding of clean and healthy living behavior. Through these activities, students can comprehend the importance of maintaining personal and environmental hygiene and put it into practice in their daily lives. Therefore, it is crucial to broaden the scope of health education activities so that more students can gain in-depth knowledge about PHBS. Involving more participants, such as families and communities, can be a strategic step in creating an environment that supports a healthy lifestyle. Awareness of the importance of clean and healthy living behavior also needs to be widely socialized, perhaps through community programs or public campaigns. Thus, health messages can penetrate and be implemented by the wider community. In other words, health education activities not only serve to enhance knowledge but also as part of the effort to form sustainable positive behaviors towards achieving optimal public health